Evolution of mutations associated with pyrethroid resistance and the reversal of resistance in Aedes aegypti - Vera Maloof, Farah Zamira, author; Black, William, advisor; McAllister, Janet, committee member; Foy, Brian, committee member; Bjostad, Louis, committee member; McGrew, Ashley, committee member (Colorado State University. Libraries, 2019)
Worldwide vector control has been relying heavily on pyrethroid insecticides to reduce Aedes aegypti Linnaeus populations. Pyrethroids are relatively inexpensive, have low vertebrate toxicity, and have been efficient in reducing mosquito populations. Constant use of pyrethroid insecticides, however, has driven mosquito populations to develop resistance over time. In this dissertation, we have tracked the evolution of three mutations in the voltage gated sodium channel (vgsc) that are associated with pyrethroid resistance Aedes aegypti populations in Mexican. These are 410, 1,016 and 1,534, corresponding to the position of amino acid substitutions in the vgsc. A valine at locus 410 (V410) confers susceptibility, while leucine (L410) confers resistance. A valine at locus 1,016 (V1,016) confers susceptibility, while isoleucine (I1,016) confers resistance. A phenylalanine at locus 1,534 (F1,534) confers susceptibility, while cysteine (C1,534) confers resistance. We performed a linkage disequilibrium analysis of the three mutations in Mexican collections from 2000–2016. In the first study, a linkage disequilibrium analysis was performed on I1,016 and C1,534 in Ae. aegypti collected in Mexico from 2000–2012, to test, in natural populations, for statistical associations between segment six (S6) in domains II and III of the vgsc. We estimated the frequency of the four di-locus haplotypes in 1,016 and 1,534: V1,016/F1,534 (susceptible), V1,016/C1,534, I1,016/F1,534, and I1,016/C1,534 (resistant). The susceptible V1,016/F1,534 di-locus haplotype went from near fixation to extinction, and the resistant I1,016/C1,534 di-locus haplotype increased in all collections from a frequency near zero, to frequencies ranging from 0.5–0.9. The V1,016/C1,534 di-locus haplotype frequency increased in all collections until 2008. After this year, the frequencies in two collections began to decrease, likely due to the fact that the I1,016/C1,534 di-locus haplotype frequency increased in all collections. However, the I1,016/F1,534 di-locus haplotype was rarely detected; for instance, it reached a frequency of only 0.09 in one collection and subsequently declined. Pyrethroid resistance in the vgsc gene appears to require the sequential evolution of two mutations. The I1,016/F1,534 di-locus haplotype appears to have low fitness, suggesting that I1,016 was unlikely to have evolved independently. Instead the C1,534 mutation evolved first but conferred only a low level of resistance. I1,016 in S6 of domain II then arose from the V1,016/C1,534 haplotype and was rapidly selected because double mutations confer higher pyrethroid resistance. This pattern suggests that knowledge of the frequencies of mutations in both S6 in domains II and III are important to predict the potential of a population to evolve kdr. Susceptible populations with high V1,016/C1,534 frequencies are at high risk for kdr evolution, whereas susceptible populations without either mutation are less likely to evolve high levels of kdr, at least over a 10 year period. In the second chapter we describe a novel replacement V410L that was initially detected in a pyrethroid resistant insectary strain from Brazilian Ae. aegypti populations. We screened V410L in 25 Ae. aegypti historical collections from Mexico. The first heterozygote appeared in 2002, and frequencies have increased in the last 16 years, along with I1,016 and C1,534. L410 showed a strong association between 1,534 and 1,016 mutations. Individuals with the triple homozygote resistant genotype had higher survival after pyrethroid exposure, 96% of the alive individuals had the triple homozygote resistant genotype after permethrin and 76% after deltamethrin treatment. The purpose of insecticide resistance management strategies is to minimize the selection for resistance to any one type of insecticide, or to help regain susceptibility in insect populations in which resistance has already arisen. A key component of resistance management assumes that there will be a negative fitness associated with resistance alleles, so that when insecticides are removed, resistance alleles will decline in frequency. In the third chapter we tested for the loss of pyrethroid resistance from eight field populations of Ae. aegypti, (six field collections from or near the city of Merida, and two collections from Tapachula and Acapulco in southern Mexico) to assess variation in the rate of loss of pyrethroid resistance. Collections were maintained for up to eight generations after pyrethroids were discontinued. We recorded changes in the frequencies of two kdr mutations, I1,016 and C1,534, and the analysis of resistance ratios (RR) with permethrin (pyrethroid type 1) and deltamethrin (pyrethroid type 2). In generations F3, F6, and F8, we also evaluated fecundity to test for parallel changes in a fitness trait during the eight generations. This was analyzed because a negative association between resistance and fecundity had previously been described in two studies [1, 2]. We demonstrate that the frequency of the Ae. aegypti pyrethroid resistance alleles I1,016 and C1,534 decline when pyrethroid pressure is removed in the laboratory; however, the pattern of decline is strain dependent. In agreement with earlier studies, fecundity was negatively associated with the frequency of resistance alleles.
Keywords: C1; I1; L 4; pyrethroids; 016 mutation; voltage gated sodium channel; 10 mutation; 534 mutation; Aedes aegypti